2020
DOI: 10.1038/s41423-020-0516-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune monitoring of interleukin-7 compassionate use in a critically ill COVID-19 patient

Abstract: One of the immune characteristics of coronavirus disease 2019 (COVID-19) is a massive fall in lymphocyte count in which magnitude associates with mortality. 1,2 Recent monitoring of COVID-19 intensive care units (ICU) patients confirmed the profound lymphopenia and its remarkable stability over time. 3,4 While most immunomodulation approaches proposed so far in COVID-19 focused on inhibiting inflammatory cytokine response; mounting evidence indicates that this viral-induced defective lymphocyte response may pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 10 publications
0
30
1
Order By: Relevance
“…Thus, the authors prospectively proposed that earlier administration of IL-7 may have indicated better clinical outcomes. 222 In a case series from St. Luc University Hospital, Brussels, Belgium, the authors showed that patients in the IL-7 treatment group seemed to have higher levels of lymphocyte counts than those in the control group, without aggravated inflammation and pulmonary injury. 223 Unfortunately, the absence of detailed phenotypic or functional studies on lymphocytes weakens the reliability of these studies.…”
Section: Cytokine-based Interventionsmentioning
confidence: 98%
“…Thus, the authors prospectively proposed that earlier administration of IL-7 may have indicated better clinical outcomes. 222 In a case series from St. Luc University Hospital, Brussels, Belgium, the authors showed that patients in the IL-7 treatment group seemed to have higher levels of lymphocyte counts than those in the control group, without aggravated inflammation and pulmonary injury. 223 Unfortunately, the absence of detailed phenotypic or functional studies on lymphocytes weakens the reliability of these studies.…”
Section: Cytokine-based Interventionsmentioning
confidence: 98%
“…In some studies, the lowest mHLA‐DR expression levels (<4,000 AB/C) were observed in patients who died. Interestingly, mHLA‐DR expression has been used for the monitoring of a critically ill COVID‐19 patient who received compassionate rhIL‐7 therapy (31). After more than 3 weeks in ICU and several episodes of recurrent infections along with constant SARS‐CoV‐2 positive PCR, mHLA‐DR expression was <4,000 AB/C.…”
Section: Clinical Results In Covid‐19 Patientsmentioning
confidence: 99%
“…After more than 3 weeks in ICU and several episodes of recurrent infections along with constant SARS‐CoV‐2 positive PCR, mHLA‐DR expression was <4,000 AB/C. After initiation of the drug, mHLA‐DR expression rapidly normalized (31). In addition, although these did not report data as AB/C, two other studies are of note: Hue et al reported a decreased mHLA‐DR in patients with COVID ARDS compared with healthy controls, but this was not as low as that found in bacterial ARDS.…”
Section: Clinical Results In Covid‐19 Patientsmentioning
confidence: 99%
“…In a case study conducted by Monneret et al (301), compassionate administration of IL-7 to a patient with severe COVID-19 significantly improved total lymphocyte count and HLA-DR expression in circulating monocytes four days after administration of the first dose. The patient also showed a significant improvement in lung involvement and negative viral load.…”
Section: Immune Cell-based Therapymentioning
confidence: 96%